DESIGN AND IMPLEMENTATION OF ANTI-TANK GUIDED-MISSILE (ATGM) CONTROL SYSTEM USING SEMI-AUTOMATIC COMMAND LINE OF SIGHT (SACLOS) METHOD BASED ON DIGITAL IMAGE PROCESSING - Muhammad Hanifudin Al Fadli; Dadang Gunawan; Romie Oktovianus Bura; Larasmoyo Nugroho (The Republic of Indonesia Defense University, 2021)
The Anti-Tank Guided-Missile (ATGM) system has a very important role in the modern battlefield. This system proved its effectiveness in many modern conflicts such as the Syrian Civil War and Nagorno-Karabakh War. The ATGM system has a very simple electronic and mechanism but it has a very high level of accuracy and precision. One of the control methods used in ATGM is SACLOS method. This method tracks missile position by detecting an infrared lamp that is placed on the missile tail. The tracking system sends control signals to the missile as a result of the correction of the missile position when flying. The infrared tracking system in this research was made using a modified OV5647 camera with the addition of a 940 nm narrow bandpass filter. There are 3 cameras with 1x, 8x, and 16x magnifications which are accessed using 3 Raspberry Pi boards. X and y coordinate data of the infrared lamp is sent to the airframe using wireless telemetry. Atmega328 microcontroller process x and y coordinate data into input proportional control. The result of this research is the prototype of an anti-tank missile control system with an infrared tracking instrument capable track a series of 88 infrared LEDs as far as 997.16 meters with a tracking speed of 90.11 FPS. The threshold parameters of image processing using luminance of YUV color space has a range of 240-255. The control parameter Kp=7 is used in wind tunnel testing with airspeed 20 m/s capable of directing airframe motion to the telescope's crosshairs.